62.5k views
2 votes
Simplify.
-2i× (-3i)
-6​

User Pztrick
by
4.9k points

1 Answer

4 votes

Answer:

(-2 i) * (-3 i) = -6

Explanation:

This is a product between imaginary numbers, so have in mind how the imaginary unit multiplies by itself:
i\,*\,i = i^2=-1

So let's work on the product:


-2\,i\,*\,(-3\,i)= (-2)\,*\,(-3)\,*\,i\,*\,i =(6)\,* i^2\,=(6)\,*\,(-1)= -6

User Wang Ruiqi
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.